Plant biotechnology and agriculture : prospects for the 21st century - Altman, A.; Hasegawa, Paul M. (Academic Press, 2012)
As the oldest and largest human intervention in nature, the science of agriculture is one of the most intensely studied practices. From manipulation of plant gene structure to the use of plants for bioenergy, biotechnology interventions in plant and agricultural science have been rapidly developing over the past ten years with immense forward leaps on an annual basis.